Gambaran Tingkat Kepuasan Poli Umum terhadap Pelayanan Laboratorium Puskesmas Naibonat Tahun 2024 - Meliana Gonsalves; Sirait, Rina Waty; Sinaga, Masrida (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
One indicator of quality at a community health center is patient satisfaction. The level of patient satisfaction with community health center services can also be seen in the laboratory service unit. The most widely used service quality measures are five dimensions of quality, namely tangibles, reliability, alertness, assurance and attention. The aim of this research is to determine the level of satisfaction of general poly patients with laboratory services at the Naibonat Community Health Center by assessing five dimensions of quality using the Importance Performance Analysis (IPA) satisfaction level analysis technique. This type of research is quantitative research with a descriptive survey research design. The population is all general poly patients who have had an examination at the Naibonat Health Center laboratory. The sample size using the Lemeshow formula was 92 respondents with a sampling technique using the accidental sampling method. The results of the satisfaction assessment for each quality dimension are based on the level of conformity, namely tangible 93.82% (very satisfied), reliability 93.02% (very satisfied), responsiveness 95.44% (very satisfied), assurance 94.61% (very satisfied) and empathy 95.69% (very satisfied). Based on the Cartesian Importance Performance Analysis (IPA) diagram, community health centers are expected to maintain the dimensions of tangible quality, alertness and attention and improve quality on several attributes in the quality dimensions of reliability and quality assurance dimensions.